(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
In this paper, we introduce pg-continuous frames and study the operators associated with a give pg-continuous frames. We also show many useful properties with corresponding notions, pg-continuous frames and pg-frames in Banach space.